(untitled) (Argos, 2025)
As is well known. Nonnus of Panopolis is the author of a massive work entitled Dionysiaca, maybe the major epic poem that has come down to us. The poet describes the antecedents of Dyonisus’ birth up to his apotheosis. Nonnus other extant work is an hexameter version of St John’s Gospel: Paraphrase of St John’s Gospel. This paper aims at three purposes: to bring up to date the data we currently count on to determine the date of the Paraphrase, to place the poem at the paraphrastic tradition and, finally, to make a brief presentation of the arguments for and against the attribution of this work to Nonnus.